Profile of Fatty Acid contents in Malaysian freshwater fish - K., Endinkeau; Tan, Kim Kiew (Universiti Putra Malaysia Press, 1993)
Nine species of Malaysian freshwater fish were analysed for their lipid and fatty acid contents. The results show that 4 species offish commonly consumed by local people contained significantly high levels offat (range 11-17% of wet weight). Malaysian freshwater fish analysed also contained high levels of unsaturated acids compared to saturated acids. The ratio of unsaturates/saturates ranged from 1.2 to 2.3. The omega-3 acids were generally low in most species analysed except for the belut sawah which contained significantly high levels in C22:6w3 (9.4/100g oil). This quantity is comparable to that of salmon, cod and herring and thus warrants consideration for commercial exploitation. Phospholipid fractions of all fish analysed (except jelawat) had polyunsaturates/saturates ratios greater than 1. O.